1988
DOI: 10.1111/j.1547-5069.1988.tb00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Reactions to Difficult Patients

Abstract: The purpose of this study was to determine whom nurses identify as difficult patients and how nurses might react to them emotionally and behaviorally. Participants (N = 73) responded to a self‐report questionnaire that contained hypothetical situations involving difficult patients. Frustration and anger were the most common reactions. The traits or behaviors that nurses reported as belonging to the most difficult patients were characteristics that are potentially modifiable. In the majority of cases the nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…The possession of experiential knowledge of endometriosis seemed to be important for quality of care, and the lack of this knowledge led some nurses to question their own competences regarding endometriosis. This suggests that there might be a link between nurses’ level of knowledge and clinical competence, and the risk for the patient of being characterized as difficult (Macdonald, 2003; Podrasky & Sexton, 1988; Trexler, 1996). Michaelsen (2012) found that if patients had certain characteristics or exhibited certain kinds of behavior, for example, “demanding, time consuming, requesting often, calling frequently, being female or uncooperative,” or having a different understanding of their illness than the nurse, they were more likely to be perceived as difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The possession of experiential knowledge of endometriosis seemed to be important for quality of care, and the lack of this knowledge led some nurses to question their own competences regarding endometriosis. This suggests that there might be a link between nurses’ level of knowledge and clinical competence, and the risk for the patient of being characterized as difficult (Macdonald, 2003; Podrasky & Sexton, 1988; Trexler, 1996). Michaelsen (2012) found that if patients had certain characteristics or exhibited certain kinds of behavior, for example, “demanding, time consuming, requesting often, calling frequently, being female or uncooperative,” or having a different understanding of their illness than the nurse, they were more likely to be perceived as difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Unco-operativeness can be a source of frustration for both doctors (Katz 1996) and nurses (Podrasky and Sexton 1988), who tend to use the term 'dif cult' to describe patients' personalities rather than their physical condition or treatment requirements (e.g. Katz 1996;Podrasky and Sexton 1988). On the other hand, some studies have indicated that unco-operativeness is associated with longer cancer survival in hospitals and with the use of fewer pain relievers or sedatives (Langer et al 1975).…”
Section: The Behaviour Of the Patient And Psychosomatic Effects On Rementioning
confidence: 96%
“…Such a lack of control is a known catalyst in stress reactions (Pomerleau and Rodin 1986) and has even been associated with the rapidity of decline and death of prisoners in concentration camps (Myers 1988). Unco-operativeness can be a source of frustration for both doctors (Katz 1996) and nurses (Podrasky and Sexton 1988), who tend to use the term 'dif cult' to describe patients' personalities rather than their physical condition or treatment requirements (e.g. Katz 1996;Podrasky and Sexton 1988).…”
Section: The Behaviour Of the Patient And Psychosomatic Effects On Rementioning
confidence: 99%
“…Nursing is distinguished by experience to a large array of potentially hectic state of affairs and circumstances. [20][21][22][23] Job stressors comprise issues such as unnecessary or soaring workloads, 24 crooked and unsocial hours of employment 25 body fatigue, 26 the poignant anxiety of dealing with ill patients and their relatives and with patients whose behaviors are barbed, 27 poor employees prop up, ambiguity regarding cure, argument with other nurses, administrator and medical staff, dealing with decease and dying, supervision obscurity, problems relating patient trouble, apprehension about methodological acquaintance and skills. 28,29 The nurses with higher works loads and burdensome responsibilities with insufficient and inefficient nursing staff endure diverse pessimistic and unconstructive higher levels of depression.…”
Section: Frustration Stress and Exploitationmentioning
confidence: 99%